Analysis of Potential Market Retribution Receipts on Poso District Revenue (PAD) Case Study in Tentena City Siwagilemba Market - Abdi Sakti Walenta; Fredrik Bastian Kawani (Universitas Negeri Makassar, 2020)
This study aims to analyze the potential acceptance of market retribution on regional revenue (PAD) in Poso district case studies on the Tentena siwagilemba market.The research method used is a qualitative method by collecting budget data and realization of market retribution income to determine the effectiveness of the potential market potential for local revenue.The results showed that the potential for market retribution still had effectiveness in the category that was quite effective with a 68 percent percentage in the management of Tentena Siwagilemba market retribution.